Natural convection in divided trapezoidal cavities filled with fluid saturated porous media - Varol, Yasin (My University, 2010)
Bölünmüş trapez kapalı ortamda akış ve ısı transferinin analizi yapılmıştır. Uniform olmayan sınır şartlarında sabit akım ve eş sıcaklık eğrileri elde edilmiştir. Gözenekli ortam şartlarında farklı Rayleigh sayılarında Nusselt sayıları hesaplanmıştır.

A numerical work was performed to determine the heat transfer and fluid flow due to forces in divided trapezoidal enclosures filled with fluid saturated porous media. In the present investigation, bottom wall was non-uniformly heated while two vertical walls were insulated and the top wall was maintained at constant cold temperature. The divider had constant thermal conductivity. Flow patterns and temperature distribution were obtained by solving numerically the governing equations, using Darcy's law. Results are presented for different values of the governing parameters, such as Rayleigh number for a porous medium, location of the partition, thickness of the partition and thermal conductivity ratio between solid and fluid media. It was observed that the conduction mode of heat transfer became dominant inside the cavity for higher thickness of the partition, low Rayleigh numbers, and low thermal conductivity ratio.
Makale - Bilimsel Dergi Makalesi - Tek Yazarlı
Keywords: Trapez Kapalı Ortam; Doğal Taşınım; Taşınım-İletim